Protecting double Holliday junctions ensures crossing over during meiosis - Shangming Tang; Sara Hariri; Regina Bohn; John E. McCarthy; Jennifer Koo; Mohammad Pourhosseinzadeh; Emerald Nguyen; Natalie Liu; Christopher Ma; Hanyu Lu; Monica Lee; Neil Hunter (Nature, 2025)
Abstract Chromosomal linkages formed through crossover recombination are essential for the accurate segregation of homologous chromosomes during meiosis 1 . The DNA events of recombination are linked to structural components of meiotic chromosomes 2 . Imperatively, the biased resolution of double Holliday junction (dHJ) intermediates into crossovers 3,4 occurs within the synaptonemal complex (SC), the meiosis-specific structure that mediates end-to-end synapsis of homologues during the pachytene stage 5,6 . However, the role of the SC in crossover-specific dHJ resolution remains unclear. Here we show that key SC components function through dependent and interdependent relationships to protect dHJs from aberrant dissolution into non-crossover products. Conditional ablation experiments reveal that cohesin, the core of SC lateral elements, is required to maintain both synapsis and dHJ-associated crossover recombination complexes (CRCs) during pachytene. The SC central region transverse-filament protein is also required to maintain CRCs. Reciprocally, the stability of the SC central region requires the continuous presence of CRCs effectively coupling synapsis to dHJ formation and desynapsis to resolution. However, dHJ protection and CRC maintenance can occur without end-to-end homologue synapsis mediated by the central element of the SC central region. We conclude that local ensembles of SC components are sufficient to enable crossover-specific dHJ resolution to ensure the linkage and segregation of homologous chromosomes.